Pengaruh Viewer Dan Subscriber Terhadap Pendapatan Youtuber Indonesia - Faisal Bachmid, Muhammad; Yuhertiana, Indrawati (Rifa'Institute, 2023)
This study aims to determine the effect of viewers and subscribers on the income of Indonesian YouTubers. The data collection techniques in this research are documentation and literature study, this research method is quantitative. Sampling in this study used non-probability sampling with a purposive sampling technique. The sample in this study amounted to 98 Indonesian YouTubers registered on the socialblade.com site. Hypothesis testing was carried out using the WarpPLS version 7.0 application. The results of this study indicate that viewers have a significant positive effect on the income of Indonesian YouTubers and subscribers have a positive effect on the income of Indonesian YouTubers, but not as large as the audience (viewers). From this study, it is hoped that future researchers can add variables related to the topic of YouTubers and can also increase the sample used to make it better and more accurate.